2017
DOI: 10.1007/s00464-017-5726-3
|View full text |Cite
|
Sign up to set email alerts
|

Trainee-associated outcomes in laparoscopic colectomy for cancer: propensity score analysis accounting for operative time, procedure complexity and patient comorbidity

Abstract: Following propensity-matched analysis of cancer patients undergoing laparoscopic colectomy, chief residents, and fellows were associated with worsened operative outcomes compared to attending along cases, while junior and mid-level resident outcomes were no different. Further study is necessary to determine what effect the PGY surgical trainee level has on post-operative morbidity in cancer patients undergoing laparoscopic colectomy in the context of multiple collinear factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Trainee participation has been associated with adverse outcomes in other specialties. In elective surgical practice, the association between trainee performance and adverse outcome is less convincing; although the procedure took longer if trainees operated (for example laparoscopic cholecystectomy and open inguinal hernia), several studies reported no increase in mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Trainee participation has been associated with adverse outcomes in other specialties. In elective surgical practice, the association between trainee performance and adverse outcome is less convincing; although the procedure took longer if trainees operated (for example laparoscopic cholecystectomy and open inguinal hernia), several studies reported no increase in mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that trainee involvement can result in improved colonic cancer detection rates at endoscopy 5 , lower bleeding complication rates in endocrine surgery 6 , and lower morbidity levels at teaching hospitals compared with non-teaching hospitals 7 . A recent study 9 has suggested that the grade of trainee may be an important factor, with senior trainee involvement associated with poorer outcomes. A recent study 9 has suggested that the grade of trainee may be an important factor, with senior trainee involvement associated with poorer outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Lens contamination events may be avoided by a skilled scope operator. Recently, as the development of laparoscopic surgery makes laparoscopic colorectal cancer surgery more prevalent in mid-sized municipal hospitals in Japan, young trainees have increasing opportunities to attend laparoscopic colorectomy procedures as a scope operator [7].…”
Section: Introductionmentioning
confidence: 99%